La discordance des temporalités dans la justice des mineurs - Ludovic Jamet (La Nouvelle Revue du Travail)
The article asks how temporal logics of action have evolved in the field of youth justice, a sector of public action that has experienced a whole host of changes over the past 20 years. New mechanisms (procedures, open rehabilitation services, placement centres, etc.) have appeared in this time, each grounded in the temporal logic of a particular action that conveys its own technical principles. The clash between these various logics has created discordant temporalities within the youth justice sector. In turn, this affects the work of its principal actors and undermines the coherence of collective action.